2022
DOI: 10.3390/nu14030488
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumption of Animal Milk Compared to Infant Formula for Non-Breastfed/Mixed-Fed Infants 6–11 Months of Age: A Systematic Review and Meta-Analysis

Abstract: Many infants do not receive breastmilk for the recommended 2-year duration. Instead, alternative milk beverages are often used, including infant formula and raw animal milk products. The purpose of this systematic review was to summarize the effect of animal milk consumption, compared to infant formula, on health outcomes in non-breastfed or mixed-fed infants aged 6–11 months. We searched multiple databases and followed Cochrane guidelines for conducting the review. The primary outcomes were anemia, gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…All children aged 6 to 23 months that did not consume cow’s milk on the previous day had lower odds of suffering from mild anemia. Cow’s milk consumption in infancy, especially the second part of infancy from 6 months to 1 year, has been associated with anemia in numerous studies due to different mechanisms such as that cow’s milk consumption decreases non-heme iron absorption in the gut and can cause intestinal bleeding in the infant [ 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Less than half of the children aged 6 to 17 months consumed non-dairy animal-source foods on the day prior to the survey, hence the children’s diet has more characteristics of a vegetarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…All children aged 6 to 23 months that did not consume cow’s milk on the previous day had lower odds of suffering from mild anemia. Cow’s milk consumption in infancy, especially the second part of infancy from 6 months to 1 year, has been associated with anemia in numerous studies due to different mechanisms such as that cow’s milk consumption decreases non-heme iron absorption in the gut and can cause intestinal bleeding in the infant [ 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Less than half of the children aged 6 to 17 months consumed non-dairy animal-source foods on the day prior to the survey, hence the children’s diet has more characteristics of a vegetarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…To update the WHO's guidance on consumption of alternative milk beverages, a systematic review assessed the effects of the consumption of animal milk compared to infant formula in non-breastfed or mixed breastfed infants aged 6-11 months [14]. See S1.1.-S1.5.…”
Section: Animal Milk and Infant Formula Feedingmentioning
confidence: 99%
“…Recent evidence continues to suggest increased risk of iron deficiency anemia from consumption of cow's milk during infancy. Meta-analyses found that consumption of cow's milk between 6-11 months of age in apparently healthy non-breastfed infants, compared to consumption of infant formula, seemed to increase the risk of anemia during infancy by two to four times (Figure 2) [14]. In addition, when considering duration of cow's milk consumption, for each additional month of cow's milk feeding, the risk of anemia increased by 23% (p < 0.001).…”
Section: Animal Milkmentioning
confidence: 99%
See 2 more Smart Citations